Perceptions of nurses about potential barriers to the use of humour in practice: a literature review of qualitative research. Issue 1 (1st February 2016) - Jones, Philippa; Tanay, Mary Anne
Abstract : Aim: To identify the perceptions of nurses (working with adult patients) about potential barriers to the use of humour in practice. Design/Methods: A literature review of qualitative research and thematic synthesis were undertaken. Four key databases were systematically searched and manual search conducted. Results: The review and thematic analysis identified five key themes from the included studies: (1) inappropriate situations, (2) being a new or junior nurse, (3) the impact on nurse professionalism, (4) differences in personality, and (5) environmental factors. Conclusion: Results from this thematic synthesis identified perceptions of nurses about potential barriers that prevent the use of humour in practice. The extent to which nurses use humour is related to personality factors, but is also affected by external and social factors. Reluctance in its use in practice is influenced by views that humour is unprofessional; with senior nurses found to have a pertinent role in influencing its use.